2020
DOI: 10.1186/s12879-020-05660-w
|View full text |Cite
|
Sign up to set email alerts
|

“Side effects--part of the package”: a mixed methods approach to study adverse events among patients being programmatically treated for DR-TB in Gujarat, India

Abstract: Background High rates of Adverse Events (AEs) during treatment is one of the leading causes of unsuccessful treatment outcomes among patients with drug resistant tuberculosis (DR-TB). However, information related to AEs is not systematically collected and managed under programmatic setting. The present study assessed the a) incidence and pattern of adverse events in first three months of DR-TB treatment initiation; b) treatment seeking behaviour for AE management; and c) explore the challenges … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
1
1
0
1
Order By: Relevance
“…Our findings revealed that almost all (99.6%) patients encountered at least one AE, with an average of four different events per patient. The frequency of AEs observed in our study was comparable with the rate reported by a study conducted in India (100%) (Jakasania et al, 2020 ), but was higher than the rates reported by studies conducted at other PMDT units in Pakistan (range: 63.7–72.3%) (Ahmad, Ahuja, et al, 2018 ; Atif et al, 2022 ), China (90.7%) (Zhang et al, 2017 ), KwaZul-Natal (80.6%) (Brust et al, 2013 ), Namibia (89%) (Sagwa et al, 2014 ), Latvia (79%) (Bloss et al, 2010 ) and Viet Nam (71.3%) (Ngoc et al, 2021 ). Variability in the frequency of AEs among published studies can be attributed to several factors.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings revealed that almost all (99.6%) patients encountered at least one AE, with an average of four different events per patient. The frequency of AEs observed in our study was comparable with the rate reported by a study conducted in India (100%) (Jakasania et al, 2020 ), but was higher than the rates reported by studies conducted at other PMDT units in Pakistan (range: 63.7–72.3%) (Ahmad, Ahuja, et al, 2018 ; Atif et al, 2022 ), China (90.7%) (Zhang et al, 2017 ), KwaZul-Natal (80.6%) (Brust et al, 2013 ), Namibia (89%) (Sagwa et al, 2014 ), Latvia (79%) (Bloss et al, 2010 ) and Viet Nam (71.3%) (Ngoc et al, 2021 ). Variability in the frequency of AEs among published studies can be attributed to several factors.…”
Section: Discussionsupporting
confidence: 92%
“…Tingkat kejadian efek samping adalah bulan pertama yang paling tinggi dibanding bulan kedua. Keluhan yang di alami yaitu diantaranya terkait sistem gastrointestinal (59, 28,3%), oftalmik (32, 15,4%) dan THT (25, 11,9%) paling sering dialami (Jakasania et al, 2020). Studi observasional cross-sectional menunjukan Sebanyak 168 pasien (132 laki-laki, 36 perempuan) menunjukan efek samping obat yang terutama melibatkan sistem pencernaan (39%), sistem perkemihan (32%), sistem musculo-skeletal (13%), sistem saraf pusat (7%), dermatologis (6%) (Singh & Pant, 2014).…”
Section: Pembahasanunclassified
“…This study adopted the use of Computer Assisted Personal Interviewing (CAPI) due to its relative advantages in integrating data collection, data entries, editing, coding, and cleaning into a single process over the traditional paper-and-pencil techniques [63], among other benefits [64,65]. The survey was based on a structured questionnaire imputed to digital software Kobocollect [66,67] and collected using tablets or mobile phones. Our key variables, which included cassava traits, the consequences of stressors, and response strategies, were measured with a representative list of items obtained from the literature, the expert review/validation workshop, the pretest of research instruments, and qualitative sessions (see Table S2).…”
Section: Data Collection and Analysismentioning
confidence: 99%